Interleukin-6 promotes tumorigenesis by altering DNA methylation in oral cancer cells - Gasche, Jacqueline Anke Katja; Hoffmann, Jürgen; Boland, C. Richard; Goel, Ajay (International journal of cancer, 2010)
Worldwide oral squamous cell carcinoma (OSCC) accounts for more than 100,000 deaths each year. Chronic inflammation constitutes one of the key risk factors for OSCC. Accumulating evidence suggests that aberrant DNA methylation may contribute to OSCC tumorigenesis. This study investigated whether chronic inflammation alters DNA methylation and expression of cancer-associated genes in OSCC. We established an in vitro model of interleukin (IL)-6 mediating chronic inflammation in OSCC cell lines. Thereafter, we measured the ability of IL-6 to induce global hypomethylation of long interspersed nuclear element-1 (LINE-1) sequences, as well as CpG methylation changes using multiple methodologies including quantitative pyrosequencing, methylation-specific multiplex ligation-dependent probe amplification and sensitive melting analysis after real-time—methylation-specific polymerase chain reaction (PCR). Gene expression was investigated by quantitative reverse transcriptase-PCR. IL-6 induced significant global LINE-1 hypomethylation (p = 0.016) in our in vitro model of inflammatory stress in OSCC cell lines. Simultaneously, IL-6 induced CpG promoter methylation changes in several important putative tumor suppressor genes including CHFR, GATA5 and PAX6. Methylation changes correlated inversely with the changes in the expression of corresponding genes. Our results indicate that IL-6-induced inflammation promotes tumorigenesis in the oral cavity by altering global LINE-1 hypomethylation. In addition, concurrent hypermethylation of multiple tumor suppressor genes by IL-6 suggests that epigenetic gene silencing may be an important consequence of chronic inflammation in the oral cavity. These findings have clinical relevance, as both methylation and inflammation are suitable targets for developing novel preventive and therapeutic measures.
Gesehen am 07.08.2023
Erstmals veröffentlicht: 12 Nov 2010